Turning the gaze: digital patient feedback and the silent pathology of the NHS - Montgomery, CM; Powell, J; Mahtani, K; Boylan, AM (Wiley, 2021)
Online review and rating sites, where patients can leave feedback on their experience of the health-care encounter, are becoming an increasing feature of primary care in the NHS. Previous research has analysed how digital surveillance is re-shaping the clinical gaze, as health-care professionals are subject to increased public monitoring. Here, we draw on an empirical study of 41 GP practice staff to show how the gaze is turning, not simply from the patient to the health-care provider, but additionally to the body politic of the NHS. Drawing on focus group and interview data conducted in five UK practices, we show how discourses of online reviews and ratings are producing new professional subjectivities among health-care professionals and the extent to which the gaze extends not only to individual health-care interactions but to the health-care service writ large. We identify three counter-discourses characterising the evolving ways in which online reviews and ratings are creating new subjects in primary care practices: victimhood, prosumption versus traditional values and taking control. We show how the ways in which staff speak about online feedback are patterned by the social environment in which they work and the constraints of the NHS they encounter on a day-to-day basis.